Profile of unaccompanied, unconscious patients in the emergency department (Journal of Institute of Medicine Nepal, 2011)
Introduction: The burden of unknown and unconscious patient is a common challenge to provide medical care in the emergency department of the hospitals. As the social security systems like insurance does not exist and poverty is rampant, it will continue in the future too. In this context this study is an attempt to analyze the morbidity & mortality as well as the types of illness, causes of unconsciousness and the source of unconsciousness in these patients without any identity. Methods: A retrospective analysis of the unaccompanied, unconscious patients attending the emergency department of Bir hospital during the Nepali year 2066 Bikram Sambat (14 April 2009 to 13 April 2010) was carried out. Results: Two-thirds of these patients were brought to hospital by the police. The next category (20%) were brought by unknown person and left without any information. Conclusions: Use of the type of substance and their nature remains unclear and there is a need to develop a trend to identify these substances so that specific treatment and hence preventive measures can be implemented effectively. Keywords: Destitute; unconscious; unknown substance DOI: http://dx.doi.org/10.3126/joim.v32i2.4936 Journal of Institute of Medicine, August, 2010; 32:2-4